(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article studies the role of human activities in causing environmental degradation and damage. It explores how human actions, such as industrialization, urbanization, deforestation, pollution, and unsustainable resource exploitation, contribute to environmental problems like climate change, loss of biodiversity, air and water pollution, and habitat destruction. Understanding the human factor in environmental damage is crucial for devising effective strategies for sustainable development and mitigating the adverse impacts on ecosystems and human well-being.